Use of intracranial translucency measurement in first trimester, beyond spina bifida (2014)
Background: The intracranial translucency (IT) is described as echolucid space Iocated in the fetal central nervous system corresponding to the fourth ventricle. Alteration in the first trimester is associated with neural tube defects (NTDs). Objective: To describe as part of the ultrasonographic assessment of the first quarter, the technical and the normal values of intracranial translucency, factors that affect its display, variability and reproducibility, diagnostic operational characteristics (sensitivity and specificity) and other utilities in the prenatal diagnosis. Methods: We conducted an electronic search of the literature registered in: PubMed, Ovid, and ProQuest, between September 2009 and January 2013. Results: It describes technical and normal values, factors affecting measurement, intra and inter-observer variability, regarding the screening and diagnosis of NTDs. Conclusion: The IT should be included in the checklist of valuable structures on 11 to 13 6/7 ultrasound; its alteration should be related not just o NTDs but posterior fossa anomalies.